2013
DOI: 10.1111/trf.12391
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cells from a rare blood donor, after freezing under good manufacturing practice conditions, generate red blood cells that recapitulate the rare blood phenotype

Abstract: Background Cultured red blood cells (cRBCs) from cord blood (CB) have been proposed as transfusion products. Whether buffy-coats discarded from blood donations (AB) may be used to generate cRBCs for transfusion has not been investigated. Study Design and Methods Erythroid progenitor cell content and numbers and blood group antigen profiles of erythroblasts (ERYs) and cRBCs generated in Human Erythroid Massive Amplification (HEMA) culture by CB (n=7) and AB (n=33, three females, three males, one AB with rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…At time 0, the frequency of CD34 + cells in MNC from AB was similar to that of CB, PV and PMF (Fig. 7A,B), consistent with the knowledge that blood donation induces stem/progenitor cell mobilization [39]. In cultures of AB without SB431542, the frequency of CD34 + cells significantly increased by 1.5–2-fold by 24–48h and became barely detectable by 72h.…”
Section: Resultssupporting
confidence: 85%
“…At time 0, the frequency of CD34 + cells in MNC from AB was similar to that of CB, PV and PMF (Fig. 7A,B), consistent with the knowledge that blood donation induces stem/progenitor cell mobilization [39]. In cultures of AB without SB431542, the frequency of CD34 + cells significantly increased by 1.5–2-fold by 24–48h and became barely detectable by 72h.…”
Section: Resultssupporting
confidence: 85%
“…We have recently shown that 3ml of blood is sufficient to culture enough cells to reprogram erythroblasts to induced pluripotent stem cells (IPSC) 41 . In addition to direct use, the expanded erythroblast can be frozen and defrosted without loss of expansion potential (data not shown), similar to what we previously reported for starting cultures from frozen PBMCs 42 . This introduces flexibility concerning actual production of products.…”
Section: Discussionsupporting
confidence: 73%
“…41 In addition to direct use, the expanded erythroblast can be frozen and defrosted without loss of expansion potential (data not shown), similar to what we previously reported for starting cultures from frozen PBMC. 42 This introduces flexibility concerning actual production of products (eg, with the generation of IPSC form cryopreserved patient material). [43][44][45] The use of adult PBMC also facilitates the availability of starting material and introduces the possibility to culture autologous cRBC.…”
Section: Discussionmentioning
confidence: 99%